Molecular Screening of KI and WU Polyomaviruses among Patients with Chronic Kidney Disease and Urinary Tract Infections - Manar Hussein AL-Aboudy; Musa Nima AL- Jiafry; Mahdi Hussein Al-Ammar (Indian Journal of Forensic Medicine & Toxicology, 2021)
KIPyV and WUPyV were recognized based on commercial standard and PCR techniques. To occurrenceof KIPyV and WUPyV DNA among chronic kidney disease (CKD) and UTI patients using VP2 gene fordetection of KIPyV and VP1 gene for WUPyV. Molecular assay results of this study revealed the presenceof KIPyV in 6 (5.3%) of CKD patients and 3 (2.7%) of UTI patients while the presence of WUPyV was1 (0.88%) in CKD patients and negative result in UTI patients. WUPyV DNA and KIPyV DNA was notdetected in plasma of healthy persons. The distribution of KIPyV and WUPyV according to gender amongCKD showed a no significance difference among both sexes in which (P value = 0.27) and (P value =0.36) respectively while the distribution of KIPyV and WUPyV among urinary tract infections showed a nosignificance difference among both sexes in which (P value = 0.13) and (P value = 0.79) respectively .Thecurrent study survey about both viruses show that female was higher than male in KIPyV in which 2 (3.22%)of KIPyV DNA were detected in male and 4 (7.84%) in female out of 113 (100%) among chronic kidneydisease patients while in urinary tract infection, patients revealed a higher percentage rate of KIPyV infemale than male in which 0 (0%) of KIPyV DNA were in male and 3 (4.54%) in female out of 111 (100%)while doesn’t detect any isolate of WUPyV in both sexes.